2006
DOI: 10.1007/s00442-006-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of microbial communities by the macrofauna: a sensitive interaction in the context of extreme summer temperatures?

Abstract: Climate models predict an increasing frequency of extremely hot summer events in the northern hemisphere for the near future. We hypothesised that microbial grazing by the metazoan macrofauna is an interaction that becomes unbalanced at high temperatures due to the different development of the grazing rates of the metazoans and the growth rates of the microbial community with increasing temperature. In order to test this hypothesis, we performed grazing experiments in which we measured the impact of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
(54 reference statements)
3
28
0
Order By: Relevance
“…Feeding rate in particular usually shows exponential or rectilinear dependencies on temperature in metazoans (e.g. Viergutz et al 2007). In this study, we recorded linear relationships between temperature and community grazing rates.…”
Section: Grazing Response To Increasing Temperaturementioning
confidence: 95%
See 3 more Smart Citations
“…Feeding rate in particular usually shows exponential or rectilinear dependencies on temperature in metazoans (e.g. Viergutz et al 2007). In this study, we recorded linear relationships between temperature and community grazing rates.…”
Section: Grazing Response To Increasing Temperaturementioning
confidence: 95%
“…Gillooly et al 2001, Savage et al 2004, growth rate (e.g. Müller & Geller 1993 and feeding rate (Montagnes et al 2001, Viergutz et al 2007). An increase in temperature generally has a stimulating effect on biological rates within a species-specific optimal temperature range.…”
Section: Grazing Response To Increasing Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Mesocosm experiments by Viergutz et al (2007) showed that summer heat waves enhance nanoplankton (\20 lm) abundances due to differential temperature responses of the plankton growth rates and the grazing rates by filter feeders. The increased abundance of nanoplankton leads to an increased grazing pressure on bacteria (usually \2 lm) and thus to shifts in plankton size structure (Weitere et al 2008).…”
Section: Changes Of Body Sizementioning
confidence: 99%